2010
DOI: 10.1177/0022429410377114
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Music Education Students’ Perceptions of Tensions Experienced During Their Undergraduate Degree

Abstract: In response to recent concern regarding music education major retention and as an effort to contribute to the “lives of teachers” scholarship in music education, the primary research question for this study was: How do undergraduate students describe their lived experiences within the instrumental music education community? Data included a questionnaire from sophomore, junior, and senior undergraduate students ( N = 34); researcher journals; 12 undergraduate student interviews; an undergraduate student focus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 18 publications
8
49
0
Order By: Relevance
“…These studies provided valuable insight into the field of student persistence in music and music education; however, more recent scholarship has encouraged researchers to focus on increasing the amount of qualitative inquiry in this field (Tinto, 2006). Conway, Eros, Pellegrino, and West (2010) examined undergraduate music education students using a qualitative methodology. These researchers investigated students' perceptions of their life experiences within the undergraduate experience, with a special focus on perceived tensions.…”
mentioning
confidence: 99%
“…These studies provided valuable insight into the field of student persistence in music and music education; however, more recent scholarship has encouraged researchers to focus on increasing the amount of qualitative inquiry in this field (Tinto, 2006). Conway, Eros, Pellegrino, and West (2010) examined undergraduate music education students using a qualitative methodology. These researchers investigated students' perceptions of their life experiences within the undergraduate experience, with a special focus on perceived tensions.…”
mentioning
confidence: 99%
“…With so much emphasis given to performer and teacher identity being separate in previous research literature, I believe this to be a major finding. Conway et al, (2010) found that music education students that participated in their study were just trying to become the best teacher and performer that they could be. Conducting is perhaps an opportunity for the music educator to work on performance skills that will have a direct, meaningful impact on their teaching ability.…”
Section: Discussionmentioning
confidence: 99%
“…Scheib (2007) concerning the existence of two identities states that possible solutions could be the increased socialization of pre-service music teachers; or, to make efforts to engage the musician-performer identity throughout one"s teaching career. Conway et al (2010), put forth the notion that many students enter college with their own musical development as a major personal goal and that views of themselves change as they continue through an undergraduate music education program. Dolloff (2006) states "[we] construct a dynamic and evolving sense of who we are through our experiences and relationships to our environment, others, and the results of our actions" (p. 125).…”
Section: Communities Of Practice As a Means To Investigate Occupationmentioning
confidence: 99%
See 1 more Smart Citation
“…Through questionnaires, interviews, and focus group sessions, Conway, Eros, Pellegrino, and West (2010) found that instrumental music education majors perceived themselves as "different" than performance majors, felt that they had more to prove within applied studios, and thought that their musician/teacher identity changed throughout the degree program. The competing demands of the performance and education areas made excelling in both difficult for these students.…”
Section: Introductionmentioning
confidence: 99%